Skematik Perencanaan Desain Ruang Terbuka Publik Di Desa Pengampon - Anang R Jatmiko; Ach. Muzajjad; Mohammad Akbar Arzidani; Rizal Dzaky Pambudi; Rahmat Hidayat; Lisa Dewi Khoiratul U; Dini Septiwulandari; Dila Retno Miaseh; Febry Eka Safitri; Sinta Nuriya (LPPI UMN AL WASHLIYAH, 2025)
Pengampon Village in Kabuh District, Jombang Regency, relies heavily on agriculture as the primary source of income. This dependence makes the local economy highly vulnerable to weather changes, commodity price fluctuations, and land conversion. To mitigate these risks, a 3D schematic design for a Public Open Space (POS) was developed as an alternative solution to promote rural economic diversification. The POS is envisioned not only as a social interaction space but also as a hub for economic and creative activities, such as local product promotion, cultural events, and collaboration among small businesses (SMEs). The planning process included site surveys, field observations, focus group discussions (FGDs) with village authorities, and participatory design finalization. The resulting 3D design provides a clear visual representation to ensure comprehensive understanding among stakeholders. It is expected that the designed POS will serve as a catalyst for sustainable community-based economic development, ultimately improving the welfare of Pengampon Village residents in the long term.